2017
DOI: 10.4037/ajcc2017266
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Stress and Anxiety in the Pediatric Cardiac Intensive Care Unit

Abstract: Background Mothers whose infants are born with complex congenital heart disease (CCHD) experience stress during their infant’s hospitalization in a pediatric cardiac intensive care unit (PCICU). Objectives This study addressed 2 research questions: (1) What are the parental stressors for mothers whose infants with CCHD are in the PCICU? And (2) What are the relationships of trait anxiety and 3 parental stressors to the parental stress response of state anxiety in mothers whose infants with CCHD are in the PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
97
1
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(119 citation statements)
references
References 30 publications
4
97
1
13
Order By: Relevance
“…Within the infant stressor category, mothers confirmed that infant appearance and behavior are a significant source of stress. Studies from both NICU and PCICU settings have found that infant appearance and behavior is the highest source of stress for mothers during the critical care admission[8, 13, 15]. Despite attempts by nurses to provide anticipatory guidance to mothers on the appearance of their infant after cardiac surgery, mothers were overwhelmed by their infant’s appearance and felt that nothing could have prepared them.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Within the infant stressor category, mothers confirmed that infant appearance and behavior are a significant source of stress. Studies from both NICU and PCICU settings have found that infant appearance and behavior is the highest source of stress for mothers during the critical care admission[8, 13, 15]. Despite attempts by nurses to provide anticipatory guidance to mothers on the appearance of their infant after cardiac surgery, mothers were overwhelmed by their infant’s appearance and felt that nothing could have prepared them.…”
Section: Discussionmentioning
confidence: 99%
“…Although survival rates have increased, morbidities are numerous, including feeding difficulties, growth failure, and long term neurodevelopmental delay[4, 5]. Parents of infants born with complex CHD experience extreme stress, often beginning during the prenatal period at the time of fetal diagnosis, and continuing during the infant’s hospitalization and postoperative course, as well as post-discharge [68]. Mothers, in particular, have very high stress levels that continue well into the first year.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations